PEMBAHARUAN PEMIKIRAN ISLAM: DASAR, TUJUAN, DAN MASA DEPAN - M. Ridwan Lubis (ILMU USHULUDDIN, 2016)
The absolute truth of religion concerns only in revelations which are revealed (matluw) and which are not revealed (ghairu matluw). The basis of this thought is that change is a must in the history of the universe including humans. This because every element of the universe always changes. The change itself is aimed to keep Islam alive as a guide so that Muslims can survive in the world and the hereafter. To ensure that Islam remains relevant to the dynamics of life, Islam must open up and respond to the change. The renewal of Islamic thought in this article will be traced from the basis, goals and development of Islam in the future. The renewal of Islamic thought is not a new but has occurred since the time of the Prophet as the case of the Prophet's dialogue with Muadz b. Jabal. The dialogue has opened the horizon to renewal of thought in order to maintain the relevance of Islam in response to changes in space and time.